The Impact of Sustainable Empowerment Interventions on Women’s Development in Nigeria - Mue, Bridget Ngunan Mue; Ogbe, Sunday John Ogbe (African Journal of Stability and Development (AJSD), 2025)
This study addresses the persistent gender disparities in Nigeria that constrain women’s economic participation and socio-cultural agency, impeding inclusive national development. Despite numerous empowerment initiatives, challenges remain regarding their sustainability and transformative impact. Employing a mixed-methods approach, the research integrates quantitative data from 361 women participants across six geopolitical zones with qualitative insights from thematic interviews, ensuring a robust triangulation of evidence. The quantitative analysis utilises descriptive and inferential statistics via SPSS, while qualitative data undergo rigorous thematic coding to capture nuanced experiences of empowerment interventions. This method provided a comprehensive understanding of measurable outcomes as well as the social dynamics influencing sustainability. Findings reveal that while recent programmes have enhanced financial inclusion and entrepreneurial growth among beneficiaries, critical gaps persist, which notably includes- inadequate knowledge management, limited integration within local governance frameworks, over-reliance on external funding, and insufficient engagement of male allies, which undermines long-term effectiveness. Furthermore, rural women remain disproportionately marginalised, partly due to literacy barriers and fragmented intervention delivery systems. The study underscores the vital role of normative transformation in reshaping gender attitudes to ensure enduring empowerment. Based on these insights, it is recommended that empowerment initiatives institutionalise knowledge management systems to safeguard operational continuity and prioritise embedding interventions within community and governance structures to enhance ownership. Diversifying funding streams through local partnerships and income-generating activities is crucial for financial sustainability. Additionally, deliberately involving male stakeholders can foster supportive environments that challenge entrenched social norms. By prioritising these strategies, programmes can move beyond short-term impacts to achieve sustainable, culturally embedded empowerment. This research contributes uniquely by advancing a holistic sustainability framework that integrates economic outcomes with normative and institutional dimensions, offering policymakers and practitioners a nuanced blueprint to enhance women’s empowerment in Nigeria and beyond.